The Impact of Korea's Economic Structural Changes since the 1990s on the Poverty Structure and Policy Implicati ons - Heesuk Yun (Korea Development Institute (KDI), 2012)
Influenced by structural changes in the economy since the 1990s, a massive number of jobs were lost and inactivity rates increased, creating groups of people suffering from long-term poverty. Households suffering from long-term or experiencing repeated poverty accounted for 27.4% of the total. These groups are mostly out of work and at the same time, they make no effort to seek out work, which indicates that they are more than likely to remain in the poverty trap. The labor force participation rate of low-educated males declined by 8.7%p, which is 14.5 times as the OECD average since 1995." "In order to overcome long-term poverty, which is the biggest challenge since Korea's economic development, it is necessary to formulate economic policies that emphasize employment generation through heightened productivity, and make structural transformation to encourage more participati on in the labor market by providing compensation while strengthening social safety net and enhancing policy effectiveness through accurate targeting. - The bottleneck phenomenon of productivity curtailed economic growth as well as alienated poverty stricken people further from the benefits of economic growth. - The real wages of the service sector, where it employs 3.6 ti mes as the manufacturing sector, has remained stagnant between 2002 and 2009, and the real income of self-employed without employees decreased by 13.9%. - The participation rate to employment insurance shows a larger gap between firms of different sizes than between regular and non-regular workers. - Stagnant service sector productivity is the main reason for the bottlenecks of income and employment generation as well as creating the vicious cycle of poverty. - Households that suffer from long-term and repeated poverty account for 27.4% of the total and 80.2% of household heads that remain in poverty during the survey period were out of work. - Loss of job leads to poverty, and finding a job leads to a way out of poverty. - The labor force participation rate of low-educated males sharply fell and 83.4% of those in constant poverty have never had job seeking experiences. - Changes in total employment rate are minimal, but the employment rate of women with intermediate or higher education increased while that of men and women with low education decreased, suggesting a change in employment composition. - Generating employment through the enhancement of service sector productivity and strengthening inter industry relationship is the key direction for policies on poverty. - It is necessary to redirect social policy towards employment support and work related income subsidy rather than providing cash support.
Keywords: 330